The impact of surgical site occurrences and the role of closed incision negative pressure therapy. (September 2016) - Willy, Christian; Engelhardt, Michael; Stichling, Marcus; Grauhan, Onnen
Abstract: Surgical site occurrences are observed in up to 60% of inpatient surgical procedures in industrialised countries. The most relevant postoperative complication is surgical site infection (SSI) because of its impact on patient outcomes and enormous treatment costs. Literature reviews ('SSI', 'deep sternal wound infections' (DSWI), 'closed incision negative pressure wound therapy' (ciNPT) were performed by electronically searching MEDLINE (PubMed) and subsequently using a 'snowball' method of continued searches of the references in the identified publications. Search criteria included publications in all languages, various study types and publication in a peer‐reviewed journal. The SSI literature search identified 1325, the DSWI search 590 and the ciNPT search 103 publications that fulfilled the search criteria. Patient‐related SSI risk factors (diabetes mellitus, obesity, smoking, hypertension, female gender) and operation‐related SSI risk factors (re‐exploration, emergency operations, prolonged ventilation, prolonged operation duration) exist. We found that patient‐ and operation‐related SSI risk factors were often different for each speciality and/or operative procedure. Based on the evidence, we found that high‐risk incisions (sternotomy and incisions in extremities after high‐energy open trauma) are principally recommended for ciNPT use. In 'lower'‐risk incisions, the addition of patient‐related or operation‐related risk factors justifies the application of ciNPT.